Insulin resistance, diabetes, and risk markers for ischaemic heart disease in Asian men and non-Asian in Bradford. Issue 5 (May 1992) - Knight, T M; Smith, Z; Whittles, A; Sahota, P; Lockton, J A; Hogg, G; Bedford, A; Toop, M; Kernohan, E E; Baker, M R
Abstract : OBJECTIVE--To examine the hypothesis, in a community not studied before, that insulin resistance associated with centralised adiposity is the mechanism underlying the predisposition of Asian immigrant communities to both ischaemic heart disease and diabetes mellitus. DESIGN--Cross sectional study within one socioeconomic stratum. SETTING--Two factories in the textile sector in Bradford, West Yorkshire. SUBJECTS--Male manual workers of Asian (110) and non-Asian origin (156) aged 20-65 years. RESULTS--Diabetes was almost three times more prevalent in the Asian group. Two hours after an oral glucose load Asian men had double the serum insulin concentrations of non-Asian men (p < 0.0001). Asian men also had significantly lower concentrations of plasma total cholesterol (p < 0.03), high density lipoprotein cholesterol (HDL) (HDL2, p < 0.0001; HDL3, p < 0.0001), and apolipoprotein AI (p < 0.0001). Fasting plasma triglyceride concentrations were slightly higher (p = 0.072) in the Asian men; thus the ratio of triglyceride cholesterol was higher (p = 0.006). The inter-relation between serum insulin and plasma lipid concentrations indicated metabolic differences between the ethnic groups. Insulin concentrations were associated with cholesterol concentrations in the Asian men only and there was a lack of association between triglyceride, low density lipoprotein cholesterol, and HDL cholesterol in this group. The risk marker profile in the Asian men was therefore quite different to that of their non-Asian counterparts and was associated with a greater tendency to centralised adiposity. CONCLUSION--These data support the insulin resistance hypothesis and thus have important implications for strategies for the prevention of heart disease in Asian communities in the United Kingdom.